2022
DOI: 10.1073/pnas.2119753119
|View full text |Cite
|
Sign up to set email alerts
|

The non-Riemannian nature of perceptual color space

Abstract: Significance For over 100 y, the scientific community has adhered to a paradigm, introduced by Riemann and furthered by Helmholtz and Schrodinger, where perceptual color space is a three-dimensional Riemannian space. This implies that the distance between two colors is the length of the shortest path that connects them. We show that a Riemannian metric overestimates the perception of large color differences because large color differences are perceived as less than the sum of small diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Additionally, we have applied our method to a study of diminishing returns in the perception of grays. Bujack et al. (2022) found that even after using a similar MLE approach to model the transformation from absolute strength to perceived strength, modeling a difference scaling function increased accuracy in predicting responses to triads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we have applied our method to a study of diminishing returns in the perception of grays. Bujack et al. (2022) found that even after using a similar MLE approach to model the transformation from absolute strength to perceived strength, modeling a difference scaling function increased accuracy in predicting responses to triads.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a slight curvature in the middle region for the plain viewing condition while, for the two light conditions, we see a dramatic effect of diminishing returns. This is perhaps unsurprising given the findings of Bujack et al. (2022) .…”
Section: Application To Empirical Data Setsmentioning
confidence: 98%
See 1 more Smart Citation
“…In their paper “The non-Riemannian nature of perceptual color space,” Bujack et al. ( 1 ) tackle the fundamental question of how to structure a color space that explains color differences as well as color matching. By deploying an elegant psychophysical procedure in which observers judged the relative magnitude of pairs of stimulus differences, they show that it is not possible to use either Euclidean or Riemannian geometry to describe both small and large perceptual color differences.…”
mentioning
confidence: 99%
“…The question asked by Bujack et al. ( 1 ) is whether it is possible to construct a Riemannian perceptual color space such that integrating the line element along the geodesic between any two points predicts larger perceptual color differences.…”
mentioning
confidence: 99%